From Reel to Real – an epilogue: Feminist politics and materiality at the London Filmmakers' Co-operative. (1st December 2017) - Jacquin, Maud
This article is an a posteriori reflection on the film programme entitled 'From Reel To Real: Women, Feminism and the London Filmmakers' Co-operative' that I curated in the context of the 50th anniversary of the LFMC. This programme, which took place at Tate Modern and Tate Britain in September 2016, gathered more than 40 films – both single screen and expanded – by 25 film-makers from different generations. In addition to attempting to situate the unique contribution of the women film-makers associated with the LFMC in relation to both experimental and feminist film, I argue that the LFMC's particular relationship with filmic materiality led the women film-makers to apprehend cinematic spectatorship but also subjectivity, the body or one's relationship with the other in ways that can be productively explored in the light of recent developments in both film and feminist theory.